All-Optical Surface Micropatterning by Electric Field Intensity Gradient. (5th November 2015) - Gertners, U.; Teteris, J.
Abstract : In this report an all-optical photo-induced formation of surface relief gratings is shown. For the surface patterning of As2 S3 and As4 S1.5 Se4.5 films a direct holographic recording setup with a 532 nm wavelength Nd:YAG CW laser light was used. Our investigations have shown that the light-induced mass transfer process strongly depends on the material itself and on the polarization of the light. It has been shown that an electric field intensity gradient has to be obtained to achieve a direct patterning. The evolution of a surface relief in relation to recording parameters and thickness of the sample has been investigated in detail.